Effects of exosomes derived from platelet-rich plasma on osteogenic differentiation of dental pulp stem cells : Effects of exosomes on osteogenic differentiation - Mo, Chuzi; Liu, Zhongjun; Lin, Yunhe; A Bu Du Xi Ku, Nu Er Bi Ya; Li, Siwei; Ruan, Qiao; Liu, Chengxia; Xu, Shuaimei; Wen, Jun (Cellular and Molecular Biology, 2024)
Platelet-rich plasma (PRP) can cause osteogenic differentiation of dental pulp stem cells (DPSCs). However, the effect of exosomes derived from PRP (PRP-Exos) on osteogenic differentiation of DPSCs remains unclear. Herein, we evaluated the impact of PRP-Exos on osteogenic differentiation of DPSCs. PRP-Exos were isolated and identified by transmission electron microscopy (TEM) and western blotting (WB). Immunofluorescence staining was performed to evaluate endocytosis of PRP-Exos by DPSCs. Alkaline phosphatase staining, alizarin red staining, western blot and qRT-PCR were carried out to evaluate the DPSCs osteogenic differentiation. The sequencing microRNA (miRNA) was conducted to determine the microRNA profile of PRP-Exos treated and untreated DPSCs. The results showed that endocytosis of PRP-Exos stimulated DPSCs odontogenic differentiation by elevated expression of ALP, DMP-1, OCN, and RUNX2. ALP activity and calcified nodules formation of PRP-Exos treated DPSCs were considerably elevated relative to that of the control group. MicroRNA sequencing revealed that 112 microRNAs considerably varied in PRP-Exos treated DPSCs, of which 84 were elevated and 28 were reduced. Pathway analysis suggested that genes targeted by differentially expressed (DE) miRNAs were contributed to many signaling cascades, such as the Wnt cascade. 65 genes targeted by 30 DE miRNA were contributed to Wnt signaling. Thus, it can be infered that PRP-Exos could enhance osteogenic differentiation and alter the miRNA expression profile of DPSCs.